THE IMPLEMENTATION OF SMART VILLAGE IN THE DEVELOPMENT OF DENAI LAMA TOURISM VILLAGE, DELI SERDANG - Dewi Yanti; Robert Sibarani; Agus Purwoko; Emrizal (Jurnal Ekonomi, 2022)
A Smart village is the result of adopting a smart city to build a town by implementing innovative and technology-based activities. This study will investigate the implementation of an intelligent town to develop the Denai Lama Tourism Village. This study aims to determine the performance of the smart village program in the Denai Lama Tourism Village and its constraints and supports. The data collection applied in this research was the qualitative research design with observations, interviews, and documentation. Based on the analysis, implementing intelligent villages in the Denai Lama Tourism Village has been unsuccessful. The results also show that what causes smart village implementation not to be successful are the weaknesses of Denai Lama Tourism Village in the application and use of technology